Association Between Diabetic Retinopathy and Periodontitis—A Systematic Review - Alvarenga, María Olimpia Paz; Miranda, Giza Hellen Nonato; Ferreira, Railson Oliveira; Saito, Miki Taketomi; Fagundes, Nathália Carolina Fernandes; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Public Health, 2021)
Background: Diabetic retinopathy is a common microvascular complication in diabetic patients and is considered the main cause of visual loss worldwide. Periodontitis is a chronic inflammatory condition, which compromises dental supporting tissues. The chronic bacterial challenge in periodontitis is a persistent source of inflammatory mediators that may be associated with insulin resistance, increasing the risk of complications of diabetes mellitus. This systematic review aimed to summarize the evidence in the association between diabetic retinopathy and periodontitis. Methods: This review was registered under the number CRD 42019142267. A search strategy in five electronic databases and a gray literature source was performed based on the PECO acronym. After data extraction, the qualitative synthesis and risk of bias analyses were performed using the Newcastle–Ottawa scale. The level of evidence of all studies taken together was evaluated through the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Results: Out of the 253 citations screened, five cross-sectional studies met the eligibility criteria and were included in the qualitative analysis, in which two were judged to be of good quality, one as fair quality, and two as poor quality. Among the included studies, a significant relationship between the severity of periodontitis (CAL > 5 mm) and the severity of diabetic retinopathy (p < 0.05) was reported by four studies. Also, an association between both diseases in non-obese adults was found after adjustments [OR 2.206 (1.114–4.366); p = 0.0232). However, the analysis of evidence by GRADE assessment was rated as low. Conclusions: Although the results of individual studies suggest an association between diabetic retinopathy and periodontitis, the quality of the body of evidence was judged to be low by the GRADE approach. Further studies with larger sample sizes, adequate models of cofounders' adjustments, and prospective analysis of periodontitis and diabetes conditions ought to be conducted to clarify this association.